PENGARUH PENDAPATAN ASURANSI TERHADAP LABA NETO PADA ENAM PERUSAHAAN ASURANSI JIWA SYARIAH DI INDONESIA - Itang Itang; Lisna Nur Apifah (Syar'Insurance: Jurnal Asuransi Syariah, 2019)
Profit or loss is usually used to assess the performance of the company's performance The main factor in determining the size of the profit is income where the size of the profit is an indicator of success or failure of management in managing the company. The formulation of the problems in this study are: 1). What is the effect of insurance income on net income of 6 Islamic life insurance companies in Indonesia?, 2). How big is the effect of insurance income on the net profit of 6 Islamic life insurance companies in Indonesia? The purpose of this study is 1). To find out whether there is an effect of insurance income on net income of 6 Islamic life insurance companies in Indonesia, 2). To find out how much influence the insurance income has on net income of 6 Islamic life insurance companies in Indonesia. The method used in this study is a quantitative method that uses a classic assumption test, hypothesis testing, correlation coefficient test and coefficient of determination test. The data used are secondary data obtained by the official website of a life insurance company. The results showed that the independent variable of insurance income had a significant effect on net income, t table of 2.04841. Because the tcount> ttable = 6.525> 2.04841 and a significance level of 0.000 because the significance value was less than 0.05 then it could be concluded that Ho was rejected and Ha was accepted .From testing the coefficient of determination (R Square) or the coefficient of determination that is equal to 0.599 so that the magnitude of the influence of Insurance Revenues on Net Profit of 0.599 = 59.9%